Steel Fiber-Reinforced Rubberised Concrete Barriers as Forgiving Infrastructure - Polydorou, Thomaida; Neocleous, Kyriacos; Illampas, Rogiros; Kyriakides, Nicholas; Alsaif, Abdulaziz; Chrysostomou, Christis; Pilakoutas, Kypros; Hadjimitsis, Diofantos G. (My University, 2018)
One of the top ten goals by the European Union’s White Paper on Transport is to reduce road fatalities. With the most vulnerable road users, motorcyclists, suffering frequent fatalities in crashes involving road barriers, the European Road Assessment has indicated the critical need to adopt improved barrier designs. While both steel guardrail and concrete barriers are encountered nowadays as road safety measures, accident statistics reveal lower numbers of motorist deaths when collisions involve concrete rather than steel. Aiming to reduce road fatality rates further by increasing the energy absorption of concrete barriers significantly, this paper investigates the incorporation of End-of-life tyre materials (e.g. steel wires and rubber particles) into concrete and the formulation of a suitable fibre-reinforced rubberised concrete mixture. The compressive strength of various rubberised concrete mixtures using cement replacements such as fly ash and silica fume was assessed experimentally, and an optimised mixture was selected. A numerical material model was calibrated based on the selected mixture. A case study barrier was simulated on LS-DYNA using the calibrated material and its performance under impact loading was investigated through numerical simulations. The scope of the paper is to present the experimental work and the resulting calibrated numerical model, and illustrate the preliminary results of the numerical study.
Keywords: Safety Barriers; Steel fibres; End-of-life tyres; Energy absorption; Impact; Resource Efficiency; Rubberised Concrete